Extending New Zealand’s Marine Shellfish Aquaculture Into Exposed Environments – Adapting to Modern Anthropogenic Challenges - Heasman, Kevin G.; Scott, Nicholas; Ericson, Jessica A.; Taylor, David I.; Buck, Bela H. (Frontiers in Marine Science, 2020)
New Zealand has a large exclusive economic zone (EEZ) of which the area between the 30 m and 50 m bathymetric zone offers the most prospects for shellfish production. Only 0.3% of this zone would be required to increase New Zealand’s shellfish production by 150 000 t. The Enabling Open Ocean Aquaculture Program, funded by the New Zealand Ministry of Busi-ness, Innovation and Employment, is a collaboration aiming to develop technologies that will enable the extension of aquaculture into New Zealand’s harsh and challenging open ocean conditions, and facilitate adaptation to the escalating effects of climate change in inner shore environments. New Zealand has started expanding aquaculture into exposed environments, allowing for farm expansion to meet increasing demand for aquaculture products but also enabling ventures into new aquatic products. Expansion into offshore developments is in di-rect response to mounting stakeholder interaction in inshore coastal areas. This document pre-sents a brief overview of the potential zones for open ocean aquaculture, the influence of cli-mate change, and two potential shellfish operational systems that may facilitate the expansion of shellfish aquaculture onto New Zealand’s exposed ocean sites.